Sustainable development of the historical city: revitalization of Bukit Mertajam through hybrid architecture approach - Hui Tian, Beh; Ismail, Sumarni; Sabil, Azmal; Setiyowati, Ernaning (Penerbit Universiti Tun Hussein Onn, 2023)
The efforts of historical city revitalization align with the United Nations key sustainable developments in protecting and safeguarding the world’s cultural and natural heritage. This study demonstrates the effectiveness of hybrid architecture as an urban catalyst in revitalizing historical cities, as a mimetic between cultural identity preservation and modernization, as employed in the townof Bukit Mertajam. By intertwining diverse elements, hybridity creates "single entities constantly changing and evolving as one," attempting to revitalize the city rather than re-proposing a single concept or idea. Numerous historic towns experienced an urban decline as a result of urbanization, modernization, and rapid social and economic transformations. Indirectly, the gentrification of traditional businesses into boutique hotels and cafes led to the collapse of local businesses and cultures. Most gentrification projects prioritize tourists' interests over the local community. The loss of sense of belonging and the degradation of local identity caused by modernization and gentrification are unavoidable for the town to sustain. There is a lack of harmony in the current gentrification in terms of a balance between socio-economic development, the authenticity of the place, and community empowerment. The study is executed through surveys, where the revitalization of Bukit Mertajam through a hybrid architecture approach is explored. This research provides a fundamental parameter for adopting measures to improve future revitalization projects in socio-economic and cultural heritage support.